Photometric and spectroscopic analysis of the Type II SN 2020jfo with a short plateau. Issue 1 (21st November 2022) - Ailawadhi, B; Dastidar, R; Misra, K; Roy, R; Hiramatsu, D; Howell, D A; Brink, T G; Zheng, W; Galbany, L; Shahbandeh, M; Arcavi, I; Ashall, C; et al.
ABSTRACT: We present high-cadence photometric and spectroscopic observations of SN 2020jfo in ultraviolet and optical/near-infrared bands starting from ∼3 to ∼434 d after the explosion, including the earliest data with the 10.4-m GTC. SN 2020jfo is a hydrogen-rich Type II SN with a relatively short plateau duration (67.0 ± 0.6 d). When compared to other Type II supernovae (SNe) of similar or shorter plateau lengths, SN 2020jfo exhibits a fainter peak absolute V -band magnitude ( M V = −16.90 ± 0.34 mag). SN 2020jfo shows significant Hα absorption in the plateau phase similar to that of typical SNe II. The emission line of stable [Ni ii ] λ7378, mostly seen in low-luminosity SNe II, is very prominent in the nebular-phase spectra of SN 2020jfo. Using the relative strengths of [Ni ii ] λ7378 and [Fe ii ] λ7155, we derive the Ni/Fe production (abundance) ratio of 0.08–0.10, which is ∼1.5 times the solar value. The progenitor mass of SN 2020jfo from nebular-phase spectral modelling and semi-analytical modelling falls in the range of 12–15 M⊙ . Furthermore, semi-analytical modelling suggests a massive H envelope in the progenitor of SN 2020jfo, which is unlikely for SNe II having short plateaus.